Knowledge-capital, Key or Enclave of Productivity in Mexican States - GERMAN SOTO, VICENTE; Vázquez de Anda, Rodrigo (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To analyze whether in Mexico, the stock of knowledge drives productivity (serves as a key factor) or is merely anchored in it (functions as an enclave).MATERIAL AND METHOD: The study uses data on knowledge-capital, productivity, capital, and income from the 32 Mexican economies during 2001-2020. A fixed-effects panel regression is applied across the 32 states for the period 2001-2020, along with spatial regressions to capture spatial autocorrelation.RESULTS: Regions with lower productivity display higher productivity-knowledge elasticities compared to those with higher productivity, a result that contrasts with other determinants such as capital per worker, per capita income, and investment efficiency. Spatial effects result in clusters of low-low and low-high values for productivity and knowledge-capital. The productivity-knowledge elasticities are higher than those of other determinants, and knowledge-capital spillovers among neighboring regions varied over time and were not always significant.CONCLUSIONS: In mexican regions, knowledge-capital is a highly influential factor (a key driver) of productivity. Therefore, policies aimed at promoting knowledge-capital will foster regional development.
Keywords: Productivity; Knowledge; Spatial correlation; Regions.